Family Psychoeducation mengurangi Tingkat Kecemasan pada Caregiver Pasien Skizofrenia di Puskesmas Sedayu 2 - Mulyanti Mulyanti; Sofyan Sofyan Indrayana (STIKes Surya Global Yogyakarta, 2022)
ABSTRACT Background: Caregivers have pivotal roles in the treatment process of people with schizophrenia. However, providing long-term care increase the risk of caregivers’ anxiety that will hamper the healing process of people with schizophrenia. Family psychoeducation is one of the interventions that is expected to reduce anxiety among those caregivers. Objective: This study aimed to prove the effect of family psychoeducation on reducing anxiety among people with schizophrenia caregivers. Methods: This quasi-experimental study with the pre-post design was conducted in the working area of Sedayu 2 Public Health Center. An Amount of 28 caregivers of people with schizophrenia were recruited from the population by using the purposive sampling technique. Participants were given family psychoeducation therapy for a month. Zung Self-Rating Anxiety Scale was administrated to collect the data. To measure the effects of intervention, the paired t-test was performed. Results: Most of participants was female (53,6%), more than 66 years old (39,3%), and more than 15 years caring for people with schizophrenia (42.9%). Paired t-test analysis showed the significant effect of the intervention (p=0,006) with the coefficient t=2.957. Conclusion: Giving family psychoeducation is effective in reducing anxiety in caregivers of schizophrenic people. Keywords: caregiver, schizophrenia, family psychoeducation, anxiety